СОВЕТ СУД-ҲУҚУҚИ ВА УЛАРНИНГ ИШ ФАОЛИЯТИ - Абдуллаев, А. (SCIENCE and SOCIETY, 2025)
Government organizations and departments that worked during the Russian Empire began to cease their activities. We can see that an expedition plan to study the activities of people’s courts was prepared and organized mainly by the People’s Commissariat of Internal Affairs and in coordination with the Commissariat of Justice.